2018
DOI: 10.1096/fasebj.2018.32.1_supplement.635.6
|View full text |Cite
|
Sign up to set email alerts
|

Cadaver vs. Microsoft HoloLens: A Comparison of Educational Outcomes of a Breast Anatomy Module

Abstract: PURPOSEMicrosoft HoloLens (HL) mixed reality technology offers students a novel modality to visualize clinically important anatomical structures, such as the breast, which are uniquely challenging to discern with the naked eye in traditional cadaveric dissection. In this study, we developed a 3‐D anatomical model of the breast and integrated it into a dynamic, educational module on the HoloLens. Here, we report the educational outcomes and overall impressions of medical students learning breast anatomy through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Previously published works utilizing HMD AR in anatomy education suggest that the ability to super‐impose virtual imaging onto real‐world surroundings improves spatial orientation and visualization of anatomical structures (Rochlen et al, 2017; Sugimoto, 2018; Yong et al, 2018). In fact, it has been suggested that one of the advantages of HMDs is the ability to visualize anatomical spatial relationships which are difficult to see directly on the body donor themselves (Sugimoto, 2018; Yong et al, 2018). This was highlighted by the students in the HoloLens dissection groups in this investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously published works utilizing HMD AR in anatomy education suggest that the ability to super‐impose virtual imaging onto real‐world surroundings improves spatial orientation and visualization of anatomical structures (Rochlen et al, 2017; Sugimoto, 2018; Yong et al, 2018). In fact, it has been suggested that one of the advantages of HMDs is the ability to visualize anatomical spatial relationships which are difficult to see directly on the body donor themselves (Sugimoto, 2018; Yong et al, 2018). This was highlighted by the students in the HoloLens dissection groups in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The overlay of the anatomical imaging itself in an AR environment involves the use of an appropriate display modality, one of those being head‐mounted displays (HMD). The benefit to using a HMD AR modality is the ability to enhance the spatial awareness of the user by allowing them to orient and move freely in space (Rochlen et al, 2017; Sugimoto, 2018; Yong et al, 2018). In comparison, other AR display modalities such as projections, or instrument and screen simulators, require more equipment in order to create the AR environment (Platts et al, 2011; Li et al, 2016; Ma et al, 2016; Manrique‐Juan et al, 2017; Kugelmann et al, 2018), which may impose more restrictions of movement in space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attractiveness for medical students, as well as no need for cadavers, appears to be the main benefit of such a teaching method. However, at the moment, virtual immersive reality as an educational tool is at its experimental stage and the benefits associated with the use of 3D holography for teaching anatomy remain unclear [8][9][10][11], even if preliminary reports are encouraging [9,[12][13][14][15][16]. Our digital project was aimed at the evaluation of the educational value of an immersive virtual reality with the use of 3D holography of the human heart.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, researchers explored different haptic hardware to simulate touch in MR environments [3,10,19,20]. At the same time, researchers studied the use of MR for learning in other areas, for example, with medical students [18,22], learning to play guitar visually [21], or learning to play piano [1,5,23]. The previous research on learning piano with MR uses overlays over physical pianos to show which key to play next.…”
Section: Introductionmentioning
confidence: 99%